THE DEVELOPMENT OF PROTECTION SYSTEMS OF STEAM TURBINES IN THE IMPLEMENTATION OF ELECTROHYDRAULIC CONTROL SYSTEMS - V. B. Novoselov; Yu. M. Brodov; E. V. Litvinov; V. V. Lebedev; A. G. Mikhailov (Известия высших учебных заведений: Проблемы энергетики)
Different schemes of protection systems used in hydrodynamic and electrohydraulic control and protection systems of steam turbines are considered, the critical analysis of their functionality is performed, the advantages of modern multi-channel protection systems are shown.